Microsecond Pulse I–V Approach to Understanding Defects in High Mobility Bi-layer Oxide Semiconductor Transistor - Hyunsuk Woo (Nature Portfolio, 2017)
Abstract The carrier transport and device instability of amorphous oxide semiconductor devices are influenced by defects that are exponentially distributed in energy, because of amorphous phase channels and front/back interfaces with a large number of sub-gap states. Thus, understanding defects and charge trapping in oxide semiconductor transistors is required for being core device element in reliable production lines. In this paper, we present the transient charging effect, the charge trapping mechanism, and the dynamic charge transport of high-mobility bilayer oxide semiconductor transistors. To this end, we exploited microsecond ramps, pulse ID–VG, transient current, and discharge current analysis methods. The mobility enhancement rate of single HfInZnO (HIZO) and bilayer HfInZnO-InZnO (HIZO-IZO) were 173.8 and 28.8%, respectively, in the charge-trapping-free environment. Transient charge trapping can be classified to temperature insensitive fast charging and thermally activated slow charging with two different trap energies. Insignificant fast transient charging of a bilayer-oxide high-mobility thin film transistor(TFT) can be explained by the low density of sub-gap states in the oxide semiconductor. Understanding defects and transient charging in the oxide semiconductor helps to determine the origin of device instability of oxide TFTs, and finally, to solve this problem.